Gulag Literature and the Literature of Nazi Camps : An Intercontexual Reading - Toker, Leona (Book collections on Project MUSE., 2019)
Devoted to the ways in which Holocaust literature and gulag literature provide contexts for each other, Leona Toker shows how the prominent features of one shed light on the veiled features and methods of the other. Toker views these narratives and texts against a background of historical information about the Soviet and Nazi regimes of repression. Writers at the center of this work include Varlam Shalamov, Primo Levi, Elie Wiesel, and Ka-Tzetnik, along with Alexandr Solzhenitsyn, Evgeniya Ginzburg, and Jorge Semprún, all of whom illuminate the discussion. Toker's twofold analysis concentrates on the narrative qualities of the works as well as how each text documents the writer's experience. She provides insight into how fictionalized narrative can double as historical testimony, how references to events might have become obscure owing to the passage of time and cultural diversity of readers, and how these references form new meaning in the text. Toker, well known as a skillful interpreter of gulag literature, offers new thinking about how gulag literature and Holocaust literature enable a better understanding about testimony in the face of evil.